Implementation of the Integrated Emergency Response System: Systematic Review - Lestari, Ayu Fina; Arso, Septo Pawelas; Jati, Sutopo Patria (Universitas Malahayati, 2024)
ABSTRACT The aim of this research is to highlight the urgency of the need for an Integrated Emergency Response System in overcoming the complexity of current global disasters and emergencies. With the need for rapid and coordinated responses, this research explores the global implementation of these systems. The focus includes integration of resources from various agencies and community participation while addressing challenges such as climate change. Given the need for a rapid and coordinated response, this research explores the application of this system globally. The focus includes integration of resources from various institutions and community participation while addressing challenges such as climate change. This research method is a systematic research that adopts the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) method. Research stages include: formulating background, objectives and research questions, as well as literature searches using related keywords in databases such as Google Scholar, PubMed, and ResearchGate. The sample consists of articles in accredited academic journals published between 2020-2023, with a focus on the Implementation of an Integrated Emergency Response System. The results of the analysis show the importance of preparation before a disaster occurs. Preparedness through health education, emergency planning, and community participation increases knowledge about emergency response. Active community involvement plays an important role in the success of an emergency management system. Factors such as resources, policies, technology, and interagency cooperation influence system implementation and response to disasters. Health system evaluation and education is an integrated strategy to improve disaster response and mitigation. Keywords: Integrated Emergency Response System, Emergency Response System and Implementation